2022
DOI: 10.1136/bcr-2021-243117
|View full text |Cite
|
Sign up to set email alerts
|

Promoting independent living and preventing lonely death in an older adult: Soma Idobata-Nagaya after the 2011 Fukushima disaster

Abstract: Contrary to the assumption that older adults are only cared for by their families in rural Japan, this case illustrates that community formation can effectively provide older adult care after an emergency as well. We look at the life of a woman who lived in a housing facility for older adults, Idobata-Nagaya in Soma, Japan, exploring how social housing—which addresses the needs of older adults regarding community, familiarity and socialising—can provide a viable, effective and comfortable environment for older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…This study revealed variations in age and independence levels among the residents, highlighting the importance of accommodating a diverse older population. Unlike traditional residential facilities with constant professional supervision, such as nursing homes, Nagaya fostered an environment for residents to interact and support each other (21). Unlike facilities with strict admission conditions based on care needs (24,25), Nagaya embraced residents with varying levels of frailty and care requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed variations in age and independence levels among the residents, highlighting the importance of accommodating a diverse older population. Unlike traditional residential facilities with constant professional supervision, such as nursing homes, Nagaya fostered an environment for residents to interact and support each other (21). Unlike facilities with strict admission conditions based on care needs (24,25), Nagaya embraced residents with varying levels of frailty and care requirements.…”
Section: Discussionmentioning
confidence: 99%
“…"Idobata" is a term used to denote a place for socializing. The amalgamation of these two terms led to the creation of "Idobata Nagaya" (hereafter Nagaya), which was designed as a hub for daily social interaction (21).Within Nagaya, residents convene for communal meals, participate in group exercise, monitor each other's health, and engage in spontaneous interactions (15,21). The overarching vision of Nagaya was to cultivate a community wherein independent older individuals could either delay the need for assisted care or remain even if their health deteriorated.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving ageing in a place during a disaster can be a challenging situation, due to various factors [6,7]. One such factor is the tendency of younger generations to establish new lives in evacuation destinations, whereas older generations prefer to remain in places where they have lived for many years [8,9]. This creates concerns about the emotional distress experienced by residents when they must relocate and adapt to new environments, leading to lifestyle changes [10].…”
Section: Introductionmentioning
confidence: 99%
“…new lives in evacuation destinations, whereas older generations prefer to remain in places where they have lived for many years [8,9]. This creates concerns about the emotional distress experienced by residents when they must relocate and adapt to new environments, leading to lifestyle changes [10].…”
Section: Introductionmentioning
confidence: 99%